Food processors' view on carbon footprinting : Describing carbon footprinting practices in Finnish food industry - Puruskainen, Ukri-Pekka (My University, 2020)
The threat of climate change drives the world leaders to mitigate greenhouse gas (GHG) emissions globally and food sector among others is under pressure to reduce its emissions rapidly. That requires changes in production methods and consumer habits. One necessary tool for enhancing greener food consumption is to provide consumers with information about food products climate impact. There are wide variation of different carbon footprinting (CF) methods, calculators, and approaches available, which without proper standardization com-promises the comparability of CF results. This thesis contributes to the literature by gathering insight from companies’ perceptions over the topic. This is done by interviewing Finnish food processors by semi-structured inter-views. The companies were asked about their current state of CF and the measures they have taken to enable or improve CF. It was found that the companies seem to perceive CF as a complex function. They have challenges with defining the scope of CF methods and con-cretely measuring the emissions, especially on production stage. The companies tend to solve this complexity by collaborating with external organizations to gain more expertise and data sources, collaborating with own supply chain partners to gain information from the processes within the supply chain, and developing own environmental impact models to identify all the sources of emissions. The results of this thesis support the view that more standardization is needed to enable globally comparable and reliable carbon footprints for food products. Especially the produc-tion stage, which often is not owned by the focal companies in food chain, needs more sup-port and guidelines to gather emission data. As for further research recommendations the findings of this thesis reveal that the similar study conducted on food producers instead of focal companies might reveal the problems closer to the emission measurement and thus tell us what should the CF guidelines and tools take into account better.

Ilmastonmuutoksen torjunta edellyttää mittavia päästöleikkauksia maailmanlaajuisesti kaikilla toimialoilla. Ruuantuotannon kohdalla päästöjen vähentäminen edellyttää muutoksia sekä ruuan tuotantoon että kuluttamiseen. Yhtenä edellytyksenä vihreämmälle kuluttajakäyttäytymiselle pidetään ruuan ilmastovaikutuksen tuomista kuluttajien tietoon. Ruuan hiilijalanjäljen määrittämiseen on tarjolla monenlaisia laskureita, viitekehyksiä ja metodeja, mikä ilman kunnollista standardointia tarkoittaa samalla monenkirjavia tuloksia hiilijalanjäljen laskennasta. Tässä työssä selvitetään elintarvikealan yritysten käsityksiä hiilijalanjälkilaskennasta haastattelemalla suomalaisia yrityksiä puoliavoimin teemahaastatteluin. Yritykset kertovat tämänhetkisistä käytännöistään hiilijalanjäljen laskentaan liittyen. Tulosten perusteella on todettavissa, että hiilijalanjäljen laskenta on yrityksille monimutkainen tehtävä. Haasteita ilmenee niin laskentaan sisällytettävien päästöjen ja toimintojen määrittämisessä kuin itse päästöjen konkreettisessa mittaamisessa, erityisesti ruuantuotannon osalta. Yritykset yrittävät vastata näihin haasteisiin yhteistyöllä ulkoisten asiantuntijoiden kanssa, yhteistyöllä omien liikekumppanien kanssa ja kehittämällä omia ympäristövaikutusmalleja laskennan tueksi. Tämän tutkimuksen tulokset tukevat jo aiemmin kirjallisuudessa muodostunutta käsitystä siitä, että standardisoinnin puute on suurimpia esteitä luotettavien ja kansainvälisesti vertailukelpoisten hiilijalanjälkien laskennassa ruokatuotteille. Erityisesti maatiloilla tapahtuvien tuotantoprosessien päästöjen selvittämiseen tarvitaan enemmän tukea toimitusketjun ulkopuolelta, koska ne eivät usein ole toimitusketjun vastuunalaisen yrityksen (focal company) omistuksessa, vaan yhden tai useamman askeleen päässä toimitusketjussa. Tämän tutkimuksen tulosten perusteella olisikin hyödyllistä tutkia seuraavaksi nimenomaan ruuan tuottajien näkemyksiä ja käsityksiä päästöjen mittaamisesta ja hiilijalanjäljen laskennasta.
Keywords: Carbon footprinting, food, greenhouse gas emissions